Biochemical and genetic properties of HPRT Cape Town - Galloon, Terry (Division of Chemical Pathology, 2017)
An unusual partial HPRT deficient mutant, HPRT Cape Town was observed to have a low activity in erythrocyte lysates at high concentrations of the purine substrates, hypoxanthine and guanine. This substrate inhibition was not observed with the substrate PPRP. The low activity was not associated with changes in the Km or Vmax for any of the substrates (Steyn and Harley, 1984). The kinetics of the proband's enzyme was studied in lymphoblast extracts. The characteristic substrate inhibition was observed which showed that this phenomenon was not confined to erythrocytes but was a more generalized phenomenon. This result implies that the decreased HPRT activity observed in the proband is due to substrate inhibition by the purine bases. The HPRT enzyme is coded for by a gene which is located on the X chromosome (Pai et al., 1980). The proband's daughter was therefore studied in order to determine the cause of the mutation. It was not known whether the substrate inhibition was the result of a mutation in the gene coding for the enzyme, a mutation which results in altered post-translational modification or the absence or alteration of factors influencing normal HPRT kinetics. The daughter's transformed lymphoblasts exhibited growth patterns in selective media that resembled those of her father. The daughter's enzyme prepared from lymphoblast extracts exhibited the characteristic substrate inhibition. These results suggest that this cell line results from the selection of a clone or clones which have suppressed the function of the X chromosome carrying the maternal and presumably normal HPRT allele. The daughter's enzyme prepared from erythrocyte lysates exhibited intermediate enzyme activity between that of the proband and a normal control. This result suggests that the daughter is an obligate heterozygote and that the defect is due to a mutation in the HPRT gene itself. The defect was studied at the gene level. No difference was observed in the banding patterns of the proband's DNA and control DNA which were digested with various restriction enzymes and hybridized to ³²p-labelled HPRT cDNA. The size of the HPRT mRNA of the proband was the same as the control. These results imply that there is no major gene alteration; this is expected since the proband only has a partial deficiency of the enzyme. The HPRT cDNA was subcloned into a riboprobe vector, pGEM-3. The T7 promoter was used to transcribe antisense RNA strands which were then hybridized to the proband's RNA and control RNA. No difference was observed in the size of the protected fragment. This result does not exclude the possibility of a point mutation as the cause of the defect in HPRT Cape Town.